Effects of Rain on Energy Metabolism while Running in a Cold Environment - Ito, R.; Nakano, M.; Yamane, M.; Amano, M.; Matsumoto, T. (International Journal of Sports Medicine, 2013)
Environmental factors tend to influence the performance of individuals who exercise for extended periods. The present study aimed to determine energy metabolism while running in cold, wet conditions using a climatic chamber that can precisely simulate rainy conditions. 7 healthy men (age, 23.3±2.9 (SD) y; height, 168.6±7.5 cm; weight, 65.9±8.1 kg; V. O2max, 52.0±5.7 mL·kg − 1·min − 1) ran on a treadmill at 70% ˙VO2max intensity for 30 min in a climatic chamber at an ambient temperature of 5°C in the presence (RAIN) or absence (CON) of 40 mm/h of precipitation. Expired air, esophageal temperature, heart rate, mean skin temperature, rating of perceived exertion and blood samples were measured. Esophageal temperature and mean skin temperature were significantly lower (P<0.05) in RAIN than in CON all. Minute ventilation, oxygen consumption and levels of plasma lactate and norepinephrine were significantly higher (P<0.05) in RAIN than in CON. In conclusion, the higher oxygen consumption and plasma lactate in RAIN indicated that energy demand increases when running in cold conditions.
Keywords: weather; climatic chamber; oxygen consumption; lactate; thermoregulatory